Pesticide induced up-regulation of esterase and aldehyde dehydrogenase in indigenous Bacillus spp. Issue 1 (2nd January 2019) - Bhatt, Pankaj; Gangola, Saurabh; Chaudhary, Parul; Khati, Priyanka; Kumar, Govind; Sharma, Anita; Srivastava, Anjana
Abstract: During bacterial growth an increased mRNA level is usually linked with higher rate of metabolism related to biodegradation of an unusual compound. In this study, quantitative gene expression data derived from mRNA level reveal the presence of pesticide degrading genes in 6 bacterial isolates showing biodegradation of cypermethrin (SG2, SG4), sulfosulfuron (SA2, Sulfo3), and fipronil (FA3, FA4). A correlation existed between the level of esterase coding mRNA and mineralization of cypermethrin in SG2 and SG4. Similarly the level of EST coding mRNA increased with biodegradation of fipronil and sulfosulfuron in FA3, FA4, SA2, and Sulfo3. Expression of est gene was observed in all the bacterial strains, but their level of expression was different. Bacterial strains SG4 and Sulfo3 showed higher level of est gene expression as compared to SG2, FA3, FA4, and SA2 and was in the range of approximately 30- to 60-fold, respectively, in comparison to control. Expression of genes for aldehyde dehydrogenase was observed in SG4 and Sulfo3. We report co expression of aldh (1000 bp) and est (∼550 bp) genes at the same time of pesticide induction/biodegradation.